Relationship of the Cranial Base and Jaw Base in Different Skeletal Patterns in Orthodontic Patients Visiting Dental Teaching Hospital - Chaulagain, Tekendra; Yadav, Rajiv; Gupta, Sanjay Prasad; Gosain, Nabin; Koirala, Pramila (Orthodontic Journal of Nepal, 2025)
Introduction: The cranial base plays an important part in determining how the mandible and maxilla relate to each other and variations in the cranial base angle, the anterior, posterior and total cranial lengths can potentially be a cause of imbalances in facial growth, and occlusion. We aimed to determine the relationship between cranial base & jaw base in different sagittal skeletal patterns among patients visiting Dental Teaching Hospital. Materials and Methods: One hundred two pre-treatment lateral cephalograms of different sagittal skeletal patterns of age >18 years (34 radiographs for each type of malocclusion with equal male and female) were obtained from the records of patients seeking orthodontic treatment in Dental Teaching Hospital, Maharajgunj Medical Campus, Institute of Medicine. A group of measurements were measured and compared among all study groups to assess the existence of any relationship between the cranial base and both jaw bases discrepancies. Mean and standard deviations were calculated. Results: The anterior cranial base length, posterior cranial base length and total cranial base length were increased in subjects with Class II sagittal skeletal patterns and decreased in Class III skeletal patterns with mean values of 66.324±2.218 and 64.632±2.193, 34.09±1.698 and 86.62±3.160 and 31.32±0.976 and 84.29±1.643 mm respectively. The cranial base angle increased in Class II and decreased in Class III with mean values of 128.12°±3.160° and 122.68°±4.650° respectively. Maxillary jaw base was increased in Class II skeletal patterns and decreased in Class III with mean values of 88.06±4.539 and 84.53±3.413 mm respectively. Mandibular jaw base and maxillomandibular difference increased in Class III and decreased in Class II with mean value 110.62±4.300 and 117.65±5.325 and 22.47±2.339 and 33.09±2.999 mm respectively. Conclusion: Cranial base and jaw base parameters showed significant relationship with Class I, II and III sagittal skeletal patterns. Cranial base and jaw base parameters except posterior cranial base and cranial base angle showed significant sexual dimorphism.